Isomorphism and its approximation in Islamic art decorations - Thalfaa Ali Mahdi Altimimi; Amin Abdel Zahra Yassin (الاكاديمي)
The current research includes four chapters , First chapter include a problem of the research which determined by [what is the isomorphism and its approximation in Islamic arts ornaments] , The second chapter includes three researches : concept of isomorphism , and references of ornamental shape , Aspects of decorative embellishment in Islamic art , as for the third chapter stated for search procedures , In light of it, the analysis was conducted in which the researcher relied on the system ,Descriptive and analytical in the process of analyzing models selected from the entire research community in accordance with the data of the content that embodies one of the sides of the concept of conformity. As for the fourth chapter, it included a number of results, including: It embodies their succession in works, formulation, performance, and type (gender) embodies a decorative composition that represents a situation Of the morphology, it led to the filling of meaning in the eyewitness through manipulation of the structural descriptions and the withdrawal of the decorative form in a way that achieves a dual function through naturalization (reading - decorative). The conclusions, including: that the ability and experience of the decorator have the most prominent role in choosing the optimal and appropriate methods of the appearance of the decorations, and they may be The adaptability and flexibility that characterize Islamic art decorations play a role in the ease of formation and combination, as these components demonstrate the artist’s ingenuity and skill in designing complex and interwoven shapes, which gives the artwork a high artistic value. The fourth chapter concluded with a proposal that could be a later study (representations of addition in the decorations of Islamic art).